1926
DOI: 10.1017/s0958841800025370
|View full text |Cite
|
Sign up to set email alerts
|

The Silted-Up Lake of Hoxne and Its Contained Flint Implements

Abstract: Before proceeding to give a description of the silted-up lake of Hoxne, and its contained flint implements, I would wish to express my thanks to Miss Dorothy Garrod, Professor P. G. H. Boswell, Sir Arthur Keith, F.R.S., Dr. O. Erdtman, Professor Henri Breuil, Mr. Alfred S. Barnes, Mr. Reginald Smith, and to Mr. Guy Maynard, for the help they have given me in my researches during 1924–6 at this spot. I am also especially indebted to the British Association, the Percy Sladen Memorial Fund, and to Mr. Henry Balfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1942
1942
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The publications and archival records that exist are almost always cursory, and aimed at historical questions no longer of pressing concern, and their testimonies are therefore often of limited value to modern Palaeolithic archaeology. Moreover, while several influential workers of the 19 th and 20 th centuries (for example Hinton and Kennard 1905;Moir 1926;Dewey and Smith 1925;King and Oakley 1936) tried to adopt the various Palaeolithic frameworks emerging from Europe (e.g. those of de Mortillet 1869, Commont 1912 andBreuil 1932), by fault or design their use and interpretation of these frameworks is idiosyncratic, imparting a particularly insular flavour to British scholarship.…”
Section: Insert Figure 1 Around Herementioning
confidence: 99%
“…The publications and archival records that exist are almost always cursory, and aimed at historical questions no longer of pressing concern, and their testimonies are therefore often of limited value to modern Palaeolithic archaeology. Moreover, while several influential workers of the 19 th and 20 th centuries (for example Hinton and Kennard 1905;Moir 1926;Dewey and Smith 1925;King and Oakley 1936) tried to adopt the various Palaeolithic frameworks emerging from Europe (e.g. those of de Mortillet 1869, Commont 1912 andBreuil 1932), by fault or design their use and interpretation of these frameworks is idiosyncratic, imparting a particularly insular flavour to British scholarship.…”
Section: Insert Figure 1 Around Herementioning
confidence: 99%
“…The evidence from Hoxne (Moir, 1927 and1935) also showed that abundant Acheulian hand-axes were found in gravel and peat associated with arctic plants and mammoth, and that hand-axes and Clactonoid flake implements continued into the overlying brickearth which contained warmer plants and animals. When we recall Breuil's observation that Acheulian hand-axes occur in cold as well as in warm stages of the Somme sequence (Breuil and Koslowski, 1931), we need not be surprised at the conclusion that the implementiferous brickearth at Westley is correlated with a glacial stage.…”
Section: Artifacts From Westley Brickearthmentioning
confidence: 98%
“…It has been widely supposed that the fragment is contemporary with the brickearth and therefore representative of Acheulian Man (Keith, 1913, Moir 1926, Montagu 1949, but there has been always an element of doubt in this supposition.…”
Section: Antiquity Of the Westley (Bury St Edmunds) Skullmentioning
confidence: 99%
“…O f the fossils which have been collected only a part have been preserved. Most of these are in the collections at Ipswich Museum and are from Moir's (1926Moir's ( , 1935 excavations, and these are listed below. The stratigraphical horizon is given where known.…”
Section: Ipswich Museummentioning
confidence: 99%
“…In addition to these records Reid (1896) recorded from his bed A, Cervus, Bos, Equus caballus and Elephas. Moir (1926) referred to remains of mammoth and reindeer from stratum B, but no teeth of the former can be traced, and the latter is based on an erroneous determination. The fragments of a right metatarsal, labelled reindeer, in the Ipswich Museum from the 1926 excavations, proved to belong to red deer when they were restored.…”
Section: Ipswich Museummentioning
confidence: 99%